2013
DOI: 10.1007/s40544-013-0024-0
|View full text |Cite
|
Sign up to set email alerts
|

Triboelectric behaviors of materials under high speeds and large currents

Abstract: Using special testers, the triboelectric behaviors of several materials were investigated in this paper under the conditions of high speeds and large currents. The obtained results revealed that the tribological behaviors and current-conducting characteristics have complicated interrelationships. Worsening in the servicing conditions can obviously deteriorate the tribological as well as electrical behaviors; high sliding speeds and large electrical currents can worsen the tribological and electrical conductivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 8 publications
0
14
0
1
Order By: Relevance
“…Electro-tribological behavior of the different variations of DLC coatings were carried out, including different humidity conditions. Unlike in electrically conductive counterparts, the electrical current was not a key parameter in these studies [4,43], because all studied DLC coatings were dielectric. The evolution of the electrical contact resistance and the coefficient of friction in the tests, typically presented a number of distinct phases.…”
Section: Electro-tribologymentioning
confidence: 99%
See 1 more Smart Citation
“…Electro-tribological behavior of the different variations of DLC coatings were carried out, including different humidity conditions. Unlike in electrically conductive counterparts, the electrical current was not a key parameter in these studies [4,43], because all studied DLC coatings were dielectric. The evolution of the electrical contact resistance and the coefficient of friction in the tests, typically presented a number of distinct phases.…”
Section: Electro-tribologymentioning
confidence: 99%
“…Monitoring of the coating status and evolution can provide a valuable tool regarding the dependability of coatings/systems in critical applications and/or difficult to access locations [25−30]. Along these lines, monitoring of the dielectric coating degradation in sliding conditions, due to wear or other coating degradation mechanisms, can be helpful in the framework of defining a predictive approach of a dependable coating operating life [4,31]. Actually, usage of DLC coatings with different electrical properties have already been studied in fatigue damage sensors [32], being crack formation and propagation one of the potential degradation mechanisms of dielectric DLC coatings.…”
Section: Introductionmentioning
confidence: 99%
“…This type is self‐powered operation, like piezoelectric acoustic sensor, converting mechanical deformation into electrical potential. The electrostatic charges can be severely affected by humidity and temperature, due to the nature electrostatic phenomenon . As one of the piezoelectric type, the surface acoustic wave (SAW) sensors consist of two bulky piezoelectric materials based rigid transducers to respond to high frequency signals above MHz .…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al. 's 1 results showed that the mechanism of material damage could transform from arcing erosion to mechanical wear with the increasing of contact load, and the wear rate was the lowest at the turning point. Especially, arcing erosion would become the dominant damage mechanism under large current and high speed.…”
Section: Introductionmentioning
confidence: 99%